Translation of King Abdullah’s speeches in the context of his media image - Ismail A. Ismail; Bella A. Bulgarova; Haya Y.J. Ashour; Sara Tabatabaei; Natalya E. Rastorgueva (RUDN Journal of Studies in Literature and Journalism)
An in-depth analysis was carried out of rhetorical approaches to the translation of the speech of King Abdullah bin Hussein of Jordan in order to identify social and humanitarian values in his speeches. The relevance of the research lies in emphasizing the importance of preserving authenticity in translation, taking into account cultural and ideological aspects, as well as the role of critical analysis of the discursive approach in understanding and transmitting values. The analysis methodology chosen by the authors of the study is complex and includes Critical Discourse Analysis (CDA), structural linguistic and rhetorical analysis, as well as comparative analysis of translations from Arabic into English. The methodology is applied in three stages: the selection of the corpus, analysis and evaluation of the effectiveness of translations. The empirical basis of the study was five texts of speeches by King Abdullah II, reflecting the social and humanitarian values of the reigning monarch. The results of the analysis reflect the humanistic orientation of the original texts, preserving concepts such as justice, responsibility, hope, solidarity, despite the fact that sometimes there is a discrepancy from the exact correspondence to the original. The authors of the article emphasize that despite this, the translations convey the monarch’s basic ideas about the importance of a world without violence, solidarity, justice and responsibility. The researchers emphasize the need to take into account cultural and ideological factors in translation in order to convey a more accurate meaning and an appropriate image of King Abdullah bin Hussein of Jordan.